(untitled) (JED (Jurnal Etika Demokrasi), 2017)
Problems in this study is the low learning outcomes and student activities Civic Grade V SDN 180 Bentengnge Bulukumba District. The goal to be achieved in this research is to increase the activity and learning outcomes of Civics with cooperative learning model type two stay two stray on grade V students SDN 180 Bentengnge Bulukumba District. This research is a classroom action research which its implementation is designed into 2 cycles. The subject of this research is the students of class V SDN 180 Bentengnge Bulukumba District 24 people. Data collection techniques in this study are test results and observation, then analyzed by using descriptive qualitative. The results showed that the application of cooperative learning model type two stay two stray can improve the activity and learning outcomes of Civics in grade V SDN 180 Bentengnge Bulukumba District. It is proven that the improvement of student learning outcomes from the first cycle with the category of Low (R) increased in cycle II with High category (T). Furthermore, the average value of cycle I is 62.75 with a complete 37.50% and increased in cycle II reaches an average value of 81.79 with 87.50% complete. Keywords: Learning Model, Cooperative Type Two Stay Two Stray, Learning Outcomes.